Assessment of clinical significance of serum uric acid, serum bilirubin and serum creatinine in patients with breast lump - Pardhan, Shoranki; Chaudhary, Anuradha; Shivhare, Rahul; Gautam, Sonveer (International Surgery Journal, 2021)
Background: Breast cancer is the most common cancer in females, approximately a quarter of all cancers. Several tumor markers are being studied now a days like α feto protein, carcinoembryonic antigen, and human chorionic gonadotropin but, the cost of these analytical methods is very high. This study is directed to assess prognostic value of serum uric acid, serum bilirubin and serum creatinine in breast lump cases. And to compare variation in benign and malignant breast lumps in relation to serum uric acid, serum bilirubin and serum creatinine values. Methods: Observational and prospective study conducted in Hamidia Hospital, Bhopal from November 2018-July 2020 included 100 patients. 50 patients were having benign breast lumps and other 50 patients malignant. Categorization of the patients done on the basis of histopathological examination. Autoanalyzer was used for estimation of serum uric acid, serum bilirubin and serum creatinine. Results: High serum uric acid level may anticipate poor prognosis in carcinoma breast, and it may perform a promising role in the management of the same. The level of serum bilirubin was slightly more or within normal range. The level of serum creatinine was within normal range in absence of any renal impairment by other etiology. Conclusions: The evaluation of serum uric acid and serum bilirubin may be useful for predicting prognosis in females with malignant breast lump and can provide help in making diagnosis during the initial assessment of the patient presenting with breast lump.